Development and Validation of a Confocal Laser Endomicroscopy-Based Score for In Vivo Assessment of Mucosal Healing in Ulcerative Colitis Patients. Issue 1 (19th December 2017) - Hundorfean, Gheorghe; Chiriac, Mircea T; Mihai, Sidonia; Hartmann, Arndt; Mudter, Jonas; Neurath, Markus F
Abstract: Background: Endoscopic monitoring is fundamental for evaluating the therapeutic response in IBD, but a validated endomicroscopic mucosal healing (MH) score is not available to date. However, confocal laser endomicroscopy (CLE) might define MH more precisely than conventional endoscopy. The major aim was to establish and validate an MH score for ulcerative colitis (UC), based on CLE. Methods: In an initial pilot study (n = 10), various CLE changes were analyzed for identification of reproducible criteria for establishing a CLE score. Four reproducible CLE criteria were implemented in a following validation study. Subsequently, active UC patients (n = 23, Mayo score ≥6) were prospectively included and underwent colonoscopy with CLE before and after 3 anti-TNF applications. Patients were clinically followed over a period of 3 years. The endomicroscopic MH score (eMHs; range, 0–4) was compared with histopathology and endoscopy scores from the same colonic location. Results: The eMHs showed high sensitivity, specificity, and accuracy values (100% with 95% confidence interval [CI] of 15.81%–100%; 93.75% with 95% CI of 69.77%–99.84%, and 94.44%, respectively). The eMHs showed a good correlation with the histological Gupta score (rs = 0.82, P < 0.0001) and the endoscopic Mayo subscore (rs = 0.81%, P < 0.0001). Sixty percent of therapy responders presented an eMHs <1, which translated into long-lasting clinical remission and reduced hospitalization, steroid, and surgery need. Conclusions: CLE can accurately assess MH based on the newly developed and statistically validated eMHs in UC, and it is superior in predicting the long-lasting clinical outcome based on both descriptive and functional barrier imaging (NCT01417728).